OPTICAL URETHROTOMY IN STRICTURES FOLLOWING FRACTURE PELVIS - Islam, Mohammad; Anwar, Farid; Ahmed, Sajjad; Ali, Azaz (Journal of Ayub Medical College Abbottabad, 2010)
Background: Management of posterior urethral injuries with pelvic fracture remains a major controversy and has always been a challenge to urologists. Objective of this study was to see the outcome of optical internal urethrotomy in treatment of urethral strictures following fracture pelvis. Methods: This prospective study was conducted at the Urology Department, Lady Reading Hospital, Peshawar from January 2007 to July 2008. A total of 45 male patients (20-60 years of age) and having urethral strictures following fracture pelvis were treated with internal optical urethrotomy. Follow-up ranged from 3 months to 1 year. Results: Fracture pelvis resulting from the road traffic accident, was the cause of urethral stricture. The good and fair results of internal optical urethrotomy were 68.56% patients who were treated with single internal optical urethrotomy. Internal optical urethrotomy was repeated in 22.86% of patients. Clean intermittent self urethral dilatation was applied as adjuvant treatment to prevent recurrence of stricture for variable period ranging from 1 to 3 months. Conclusion: Internal optical urethrotomy is safe and effective procedure for short yet inaccessible strictures from the perineum. Keywords: Pelvic Fracture, Stricture urethra, Internal optical urethrotomy, outcome, dilatation